Before AIDS : gay health politics in the 1970s - Batza, Katie (Politics and culture in modern America., 2018)
Before AIDS chronicles the development of gay health services in the 1970s as gay men faced public health challenges stemming from both their political marginalization and disease. Activists using tools and tactics from across their era's political landscape built a nationwide gay medical system, changing ideas about sexuality and health.